Nalbuphine inhibits remifentanil-induced hyperalgesia in rats - PANG Hong-li, LI Hong-ying, HE Dong-hai, XU Yuan-zheng, ZHENG Xiao-zhen (Jichu yixue yu linchuang, 2020)
Objective To investigate the effect of nalbuphine on hyperalgesia induced by remifentanil and its mechanism. Methods Rats were divided into the control group,remifentanil group (R group),incisional pain model group(M group),remifentanil and incisional pain model group(RM group),nalbuphine pretreatment group(N+RM group). The R group,RM group,N+RM group were intravenously infused with remifentanil 1.0 μg/(kg·min),the M group,RM group and N+RM group were constructed incisional pain model by pelmatic incision operation and the N+RM group was intravenously injected with nalbuphine 0.6 mg/kg before remifentanil. The paw withdrawal thermal latency (PWL) and paw withdrawal mechanical threshold (PWT) were measured 24 hours before modeling (T-1),2 hours after modeling(T1),6 hours after modeling(T2),24 hours after modeling(T3) and 48 hours after modeling (T4).Western blot was conducted to detect the expression of NR1,NR2A,NR2B,ERK1/2 and p-ERK1/2 at T4. Results Compared with the control group,the PWL and PWT,the expression of NR1,NR2B,p-ERK1/2 and p-ERK/ERK increased significantly in all other groups(P＜0.05). Compared with the M group, the PWL and PWT, the expression of NR1,NR2B,p-ERK1/2 and p-ERK/ERK increased significantly in RM group(P＜0.05). Compared with the RM group,the PWL and PWT,the expression of NR1,NR2B,p-ERK1/2 and p-ERK/ERK decreased significantly in N+RM group(P＜0.05). Conclusions Naborphine can antagonize hyperalgesia induced by remifentanil.